miRNome profiling of LSC-enriched CD34+CD38−CD26+ fraction in Ph+ CML-CP samples from Argentinean patients: a potential new pharmacogenomic tool - Ruiz, María Sol; Sánchez, María Belén; Bonecker, Simone; Furtado, Carolina; Koile, Daniel; Yankilevich, Patricio; Cranco, Santiago; Custidiano, María del Rosario; Freitas, Josefina; Moiraghi, Beatriz; Pérez, Mariel Ana; Pavlovsky, Carolina; et al. (Frontiers in Pharmacology, 2021)
Chronic myeloid leukemia (CML) is a myeloid stem cell neoplasm characterized by an expansion of myeloid progenitor cells and the presence of BCR-ABL1 oncoprotein. Since the introduction of specific BCR-ABL1 tyrosine kinase inhibitors (TKI), overall survival has improved significantly. However, under long-term therapy patients may have residual disease that originates from TKI-resistant leukemic stem cells (LSC). In this work, we analyzed the miRNome of LSC-enriched CD34+CD38-CD26+ and normal hematopoietic stem cells (HSC) fractions obtained from the same chronic phase (CP) CML patients, and stem and progenitor cells obtained from healthy donors (HD) by next-generation sequencing. We detected a global decrease of microRNA levels in LSC-enriched CD34+CD38-CD26+ and HSC fractions from CML-CP patients, and decreased levels of microRNAs and snoRNAs from a genomic cluster in chromosome 14, suggesting a mechanism of silencing of multiple non-coding RNAs. Surprisingly, HSC from CML-CP patients, despite the absence of BCR-ABL1 expression, showed an altered miRNome. We confirmed by RT-qPCR that the levels of miR-196a-5p were increased more than 9-fold in CD26+ (BCR-ABL1+) vs. CD26- (BCR-ABL1-) CD34+CD38- fractions from CML-CP patients at diagnosis, and in silico analysis revealed a significant association to lipid metabolism and hematopoiesis functions. In the light of recent descriptions of increased oxidative metabolism in CML LSC-enriched fractions , these results serve as a guide for future functional studies that evaluate the role of microRNAs in this process. Metabolic vulnerabilities in LSCs open the road for new therapeutic strategies. This is the first report of the miRNome of CML-CP CD34+CD38- fractions that distinguishes between CD26+ (BCR-ABL1+) and their CD26- (BCR-ABL1-) counterparts, providing valuable data for future studies.